The Relationship Between Collaborative Skills and Chemistry Learning Achievement - Raihanah, Dinnah; Ridwan, Achmad; Rahmawati, Yuli (Universitas Negeri Medan, 2025)
Abstract: This study investigates the relationship between students’ collaborative skills and their achievement in chemistry learning, particularly on the topic of acid–base concepts. Collaborative ability plays an essential role in supporting effective learning and knowledge construction, especially in cooperative classroom settings. The research involved 255 eleventh-grade students who completed both a collaborative skills questionnaire and a chemistry achievement test. The collaborative skills instrument consisted of 23 items covering 11 dimensions, while the achievement test assessed students’ understanding of acid–base concepts. Data were analyzed using Spearman’s correlation after confirming normality and identifying a non-linear relationship. The results revealed a positive and significant correlation between collaborative skills and learning achievement (r = 0.501; p < 0.001), with a determination coefficient of 25.1%. These findings indicate that students with stronger collaborative skills tend to achieve higher levels of conceptual mastery in chemistry. Overall, the study emphasizes the importance of developing collaboration competencies to enhance academic performance in science learning.